2008
DOI: 10.1007/s00428-007-0559-4
|View full text |Cite
|
Sign up to set email alerts
|

Hibernoma-like brown fat in the bone marrow: report of a unique case

Abstract: We report on a bone-marrow biopsy of a 61-year-old female patient that was performed because of the clinical suspicion of a myeloproliferative disease. The trephine biopsy showed morphological features that were consistent with an essential thrombocythaemia (ET). The diagnosis of a myeloproliferative disease could be corroborated by demonstration of the V617F mutation of JAK2. Besides the histological features of ET, the marrow showed a peculiar infiltrate that consisted of multivacuolated cells that were immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 7 publications
1
19
0
2
Order By: Relevance
“…The existence of BAT in bone marrow (BM), which attenuates with aging and diabetes, was reported in mice (Krings et al, 2012). Also, a nontumorous infiltration of BAT in human BM was reported in a case of essential hyperthrombocythemia (Thorns et al, 2008). A functional link between BM fat and hematopoiesis was first reported by Dexter et al (Dexter et al, 1977), who showed that BM adipocytes with mitochondria-attached multilocular lipid droplets were essential for the maintenance of colony-forming units-spleen (CFU-S), a short-term repopulating hematopoietic progenitor cell (HPC) distinct from hematopoietic stem cell (HSC).…”
Section: Introductionmentioning
confidence: 99%
“…The existence of BAT in bone marrow (BM), which attenuates with aging and diabetes, was reported in mice (Krings et al, 2012). Also, a nontumorous infiltration of BAT in human BM was reported in a case of essential hyperthrombocythemia (Thorns et al, 2008). A functional link between BM fat and hematopoiesis was first reported by Dexter et al (Dexter et al, 1977), who showed that BM adipocytes with mitochondria-attached multilocular lipid droplets were essential for the maintenance of colony-forming units-spleen (CFU-S), a short-term repopulating hematopoietic progenitor cell (HPC) distinct from hematopoietic stem cell (HSC).…”
Section: Introductionmentioning
confidence: 99%
“…35 This idea is also supported by the fact that so-called hibernomas, rare and benign tumors consisting of brown adipocytes, can develop in bone marrow. 36,37 Recently, it was shown that MAT has a distinct phenotype resembling both WAT and BAT. 38 The authors showed that MAT expresses several BAT-selective genes including Prdm16, Dio2 and Pgc1α at similar levels as in the interscapular BAT depot.…”
Section: Bat and Thermogenic Adipocytesmentioning
confidence: 99%
“…Nishio et al (2012) developed an alternative approach to reprogram hES and IPS cells into functional brown adipocytes both in vitro and in vivo with an efficiency of O90% without utilizing exogenous gene transfer. The protocol was initially discovered by observations that conditions which were established to differentiate cells of the haematopoietic lineage resulted in the production of significant numbers of brown adipocytes (Thorns et al 2008, Krings et al 2012. They employed a haemopoietic cocktail (HC) composed of KIT ligand (KITGL), fms-related tyrosine kinase 3 ligand (FLT3LG), interleukin 6 (IL6), and VEGF along with the previously reported BAT inducer BMP7 (Tseng et al 2008).…”
Section: Brown Adipocytes Differentiated From Hes and Ips Cellsmentioning
confidence: 99%